196k views
1 vote
To factor 9x^2-4 you can first rewrite the expression as

1 Answer

7 votes

Answer:


(3x)^2 - 2^2

Explanation:

The given expression is
9x^2 - 4

We can write
9x^2 = 3*3*x^2 = 3^2.y^2 = (3y)^2 and 4 can be written as square of 2. 4 =
2^(2)

Therefore, we can write
9x^2 - 4 = (3x)^2 - 2^2

Now we can factor it out.

We are asked to rewrite the expression.

Therefore, the answer is
(3x)^2 - 2^2

Let me factor this expression for your reference.


(3x)^2 - 2^2 = (3x -2)(3x +2)

User Jonas Kaufmann
by
5.4k points